Emergenza epidemiologica e obblighi di rinegoziare nei contratti del calcio professionistico - Polidori, S. (Revista de Actualidad Jurídica Iberoamericana, 2020)
The COVID-19 epidemiological emergency had devastating effects on the Italian economy, especially in the professional football industry. The football competitions break and uncertainty about their recovery cause a revenue block against unchanged costs. Therefore, football companies have to renegotiate the terms of contracts with their athletes and members. Specifically, having a collaborative behaviour based on good faith is a real duty while renegotiating members` contracts. This paper addresses some of the solutions that football referees` committees would find in case of legal conflicts in the near future.